Motivators and barriers for physical activity in older workers: a socio-ecological exploration - Mohd Mohadis, Hazwani; Mohamad Ali, Nazlena; Shahar, Suzana (Universiti Kebangsaan Malaysia Medical Center (UKMMC), 2016)
Recognising the importance of physical activity in preventing the development of chronic diseases, this study aims to investigate motivators and barriers of physical activity among older workers based on a socio-ecological model. Twenty-five older workers aged 50-75 years participated in a series of in-depth interview sessions. Using thematic analysis, transcripts were coded and categorised into motivators and barriers of physical activity. The motivators are health concerns, early exposure to physical activity, companionship, moral support, expert advice and workplace policy. In contrast, physical environment, cultural norms and social stigma have become the barriers leading to physical inactivity. Meanwhile, attitude, nature of work and facilities can be both motivators and barriers. This study provides baseline knowledge on the factors influencing physical activity behaviour at multiple socio-ecological levels, which need to be considered in developing physical activity intervention targeting older workers.